Termite Biodiversity in Gunung Walat Education Forest, Sukabumi - Noor Farikhah Haneda; Andri Firmansyah (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2012)
Termites are social insects that are polimorfis that live in a colonial. It has a caste system. Each caste has different body morphology. The warrior caste has the typical form of mandible. Termites can be identified by observing the size of head as well as the mandibel of the warrior caste. This research aims to know the diversity of termites in Mount Walat Education forest, Sukabumi, West Java. Termites were found preserved in film canisters containing alcohol 70%. Based on research results from five locations namely termites at the stands of agathis, pine, puspa, agroforestri and around the mess (Inn). Schedorhinotermes is a genus of the family Rhinotermitidae members most often encountered, from twenty-six instances gained thirteen of which were species of termites from members of the genus Schedorhinotermes. Thirteen other termites example i.e. genus Macrotermes, Odontotermes, with a total of six and five respectively while the genus Pericapritermes and Nasutitermes respectively amounted to a single instance.